Manajemen Zakat dalam Konstruksi Akuntansi Modern - Puteri Amanda Ardita; Hilya Diniya; Nia Amellia; Niharotul Fauzia (SIL'AH: Jurnal Ekonomi Syariah, 2025)
Zakat has tremendous potential to strengthen the existence of Islam and bring about social change through public finance. However, to optimise the benefits of zakat, good management based on Islamic sharia principles is required. This study aims to explore the principles of zakat in the context of modern accounting from a theoretical and practical perspective. The research method employs a qualitative approach using secondary data in the form of literature reviews. This study advocates for effective and efficient zakat management through the application of Islamic sharia principles in zakat accounting. The results of this study indicate that zakat integrity is an important aspect of zakat management that needs to be considered in modern accounting systems. This includes zakat management, zakat distribution, and zakat fund management. This study contributes to the importance of proper harmonisation between zakat principles and accounting standards. This is so that more comprehensive information can be provided to relevant parties in zakat management